2017
DOI: 10.1136/bmjopen-2017-016600
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean sections and private insurance: systematic review and meta-analysis

Abstract: ObjectiveFinancial incentives associated with private insurance may encourage healthcare providers to perform more caesarean sections. We therefore sought to determine the association of private insurance and odds of caesarean section.DesignSystematic review and meta-analysis.Data sourcesMEDLINE, Embase and The Cochrane Library from the first year of records through August 2016.Eligibility criteriaWe included studies that reported data to allow the calculation of OR of caesarean section of privately insured as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 54 publications
5
44
0
Order By: Relevance
“…Our findings confirm the studies by Hoxha and colleagues [18][19][20] where they argue that women with private health insurance are more likely to undergo CS than those with public insurance or no insurance at all. Women with private/employer insurance have higher probability to have CS compared to those with no insurance cover (aRRR = 1.6064).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings confirm the studies by Hoxha and colleagues [18][19][20] where they argue that women with private health insurance are more likely to undergo CS than those with public insurance or no insurance at all. Women with private/employer insurance have higher probability to have CS compared to those with no insurance cover (aRRR = 1.6064).…”
Section: Discussionsupporting
confidence: 92%
“…As for the potential explanatory variables, we selected them based on previous literature [11,[17][18][19][20][21][22][23][24][25][26][27]. We categorized them into several groups, namely spatial variables, maternal variables, demographic variables, access to information, and socio-economic variables.…”
Section: Variables Selectionmentioning
confidence: 99%
“…Insurance coverage is one of the health system factors known to influence the use of medical procedures,15 16 including CS 17–20. While private insurance, for example, seems to increase the odds of having a CS delivery,17 the lack of insurance appears to decrease it 20–22.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the adverse outcomes concerning equity and the doubtful gains in efficiency, private provision and finance of healthcare can result in unnecessary, and sometimes harmful, cases of overtreatment. A systematic review of 21 studies [21] found that the odds of a Caesarean section (C-section) being performed was significantly higher in relation to women with private health insurance compared with women using public health insurance. In Chile, for example, three out of four publicly insured women who opt to give birth in a private hospital will have a C-section, while in public hospitals only one out of four women will undergo this procedure [22,23].…”
Section: Introductionmentioning
confidence: 99%